2020
DOI: 10.31557/apjcp.2020.21.4.1063
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ki-67 Labeling index and Histopathological Grading of Glioma in Indonesian Population

Abstract: Background: Gliomas are the most frequent primary brain tumors. According to World Health Organization guidelines, gliomas are graded into four groups (Group I-IV). This histological grading will determine prognosis and treatment of the patient. Morphological criteria are not always accurate. Tumor proliferation index is a potent quantitative marker for tumor behavior and prognosis, also it's the basis of gliomagenesis. Ki-67 immunohistochemistry examination for determining proliferation index has been suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…The patients in the high-quality group received high-quality nursing plus comprehensive nursing. The specific methods are as follows: upon admission, the nursing staff help the patients quickly familiarize the treatment environment to facilitate their following treatment cooperation: the patients were instructed and accompanied by nursing staff in various preoperative and postoperative physical examinations to reduce their psychological pressure [ 7 ]; 1-2 days preoperatively, the patients were given operation precautions and health education to avoid perioperative stress and help them to better understand the disease and stabilize their emotions; cases with similar treatment procedures were introduced to the patients to eliminate their anxiety and fear [ 8 ]; 1 day preoperatively, the patients were given perioperative information such as operating room environment, anesthesia methods, and the general procedure of the operation; 30 minutes preoperatively, the patients were comforted when entering the operation room to help them to eliminate anxiety and fear; the preoperative preparation after anesthesia such as indwelling urinary catheter was performed to reduce the discomfort of the patient [ 9 ]; invasive operations such as venous blood collection and intravenous infusion were performed by skilled nurses after surgery; and the patients' conditions were strictly monitored to promptly resolve their issues [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The patients in the high-quality group received high-quality nursing plus comprehensive nursing. The specific methods are as follows: upon admission, the nursing staff help the patients quickly familiarize the treatment environment to facilitate their following treatment cooperation: the patients were instructed and accompanied by nursing staff in various preoperative and postoperative physical examinations to reduce their psychological pressure [ 7 ]; 1-2 days preoperatively, the patients were given operation precautions and health education to avoid perioperative stress and help them to better understand the disease and stabilize their emotions; cases with similar treatment procedures were introduced to the patients to eliminate their anxiety and fear [ 8 ]; 1 day preoperatively, the patients were given perioperative information such as operating room environment, anesthesia methods, and the general procedure of the operation; 30 minutes preoperatively, the patients were comforted when entering the operation room to help them to eliminate anxiety and fear; the preoperative preparation after anesthesia such as indwelling urinary catheter was performed to reduce the discomfort of the patient [ 9 ]; invasive operations such as venous blood collection and intravenous infusion were performed by skilled nurses after surgery; and the patients' conditions were strictly monitored to promptly resolve their issues [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Theresia et al. ( 18 ) demonstrated an association between the Ki-67 labeling index and the histopathological grade of glioma, with LGG having a significantly lower grade than HGG. Ki-67 expression may be utilized to quantify lymphocyte proliferation ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…found an association between the Ki-67 labeling index and histopathological grading of glioma. LGG patients had a significantly lower Ki-67 labeling index than HGG patients, and a cut-off of 10% was used to differentiate LGG from HGG ( 18 , 19 ). The relationship between Ki-67 expression and IDH1 mutation status demonstrated by Zeng et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic grade and the Ki-67 labeling index are used to help predict biologic behavior and prognosis of gliomas. 72 A recently published study has demonstrated that radiomics features based on T2 FLAIR images have been shown to preoperatively correlate and predict multiple immunohistochemical features of gliomas such as Ki-67, S-100, vimentin, and CD34 expression. 49 These insights are expected to enhance the personalized treatment of patients with gliomas.…”
Section: Technologic Methods and Computational Processmentioning
confidence: 99%